The Effect of Soursop (Announa Muricata L.) Leaves Powder on Diameter of Muscle Fiber, Lipid Cell, Body Weight Gain and Carcass Percentage of Tegal Duck - Tugiyanti, Elly; Mawarti, Nur; Rosidi, Rosidi; Harisulistyawan, Ibnu (ANIMAL PRODUCTION, 2017)
The present study investigated the supplementation of soursop leaves powder (Annona muricata L.) on body weight gain and carcass percentage of male Tegal duck. Research was conducted from 29 November 2015 to 3 January 2016 in duck cage in Sokaraja Kulon, Purwokerto. One hundred male Tegal duck were fed basal feed consisted of 30% corn, 7% soy bean meal, 6,1% vegetable oil, 17% poultry meat meal, 38,2% ricebran, 0,1% L-lysin HCL, 0,3% DL-methionin, 0,2% topmix, 0,1% NaCl, and 1% CaCO3. Experimental research used completely randomized design with treatments composed of basal feed plus 0, 5, 10, and 15% soursop leaves meal, each with 5 replicates. The observed variables were diameter of muscle fiber, lipid cell, body weight gain, and carcass percentage. The obtained data were subject to analysis of variance followed by orthogonal polynomial test. Result showed that treatments affected non significantly (P>0.05) to the diameter of chest muscle fiber, carcass percentage and carcass but significantly affected (P<0,05) body weight gain with equation Y  =  427,74  - 67,10 X  + 2,27 X2..  Conclusively, supplementation of soursop leaves meal (Annona muricata L.) in feed has not been able to increase the muscle fiber diameter of intermuscular lipid cell, carcass percentage and carcass parts. Excessive supplement even lowers the body weight gain of male Tegal duck.